1996
DOI: 10.1210/jcem.81.11.8923843
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol, dehydroepiandrosterone (DHEA), and DHEA sulfate in the cerebrospinal fluid of man: relation to blood levels and the effects of age.

Abstract: The relation between blood and cerebrospinal fluid (CSF) concentrations of cortisol, dehydroepiandrosterone (DHEA), and its sulfate (DHEAS) was measured in 62 subjects aged 3-85 yr old, fitted with ventriculo-peritoneal or lumbar-peritoneal shunts for a variety of diagnoses. There were 36 males and 36 females. Forty-eight subjects were not taking exogenous corticosteroids; the other 14 were receiving either systemic or local steroids. A single sample of blood and CSF was taken from each subject within 10 min f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 45 publications
4
45
0
4
Order By: Relevance
“…46 Animals studies in rodents have generally found memory-enhancing effects, 47 antidepressant-like effects, 48 antianxiety effect, 49 and neurotrophic effects. 50,51 In humans, levels in circulation decline with age, 52 with chronic stress and medical illness. 53 DHEA and DHEA-S may physiologically buffer the effects of excessive glucocorticoid exposure.…”
Section: Hpg Axismentioning
confidence: 99%
“…46 Animals studies in rodents have generally found memory-enhancing effects, 47 antidepressant-like effects, 48 antianxiety effect, 49 and neurotrophic effects. 50,51 In humans, levels in circulation decline with age, 52 with chronic stress and medical illness. 53 DHEA and DHEA-S may physiologically buffer the effects of excessive glucocorticoid exposure.…”
Section: Hpg Axismentioning
confidence: 99%
“…The few studies on serum cortisol in healthy children between the ages of 2 and 18 years reported similar large interindividual variability and also failed to find correlations with age (Guazzo et al 1996;Knutsson et al 1997). In contrast, studies that measured cortisol in saliva samples in children have found agerelated increases (Lupien et al 2001), with the most prominent age associations occurring between years 10 and 12 (Lupien et al 2001) and during adolescence (Netherton et al 2004;Walker et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Parallel experiments showed that, although DHEAS also protected neurons in vitro against NMDA, it seemed less potent because significant protection only was observed at Ϸ10 times the lowest effective dose of DHEA (10 nM) used in these experiments. It is therefore interesting to note that, although levels of DHEAS in the blood of adult humans are more than 100 times those of DHEA, in the CSF, the ratio is only about three times (17). This suggests that DHEA may play a predominant role in the combined neuroprotective effects of these steroids in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that DHEA may play a predominant role in the combined neuroprotective effects of these steroids in the brain. However, radioimmunoassays showed that the neuroprotective action of DHEAS is not due to conversion to DHEA, so DHEAS may contribute directly to the overall protective actions in species, such as humans, that have appreciable amounts of both steroids in their CSF (17). The protective actions of DHEA(S) stand in contrast to those of glucocortoids, which induce hippocampal pyramidal neuron degeneration (10).…”
Section: Discussionmentioning
confidence: 99%